Effect of general anesthetics on the developing brain - S Velayudha Reddy (Wolters Kluwer Medknow Publications, 2012)
Studies on rodents and subhuman primates suggest that prolonged exposure to general anesthetics may induce widespread neuronal cell death and neurological sequelae; seriously questioning the safety of pediatric anesthesia. This review presents recent developments in this rapidly emerging field. There is mounting and convincing preclinical evidence in rodents and nonhuman primates that anesthetics in common clinical use are neurotoxic to the developing brain in vitro and cause long-term neurobehavioral abnormalities in vivo. Prior to the publication of animal data and after the publication of animal data, there are several human cohort studies that demonstrate the association of poor neurodevelopmental outcome in neonates, who underwent major surgery during their neonatal period. This review summarizes our present understanding of some of the key components responsible for anesthesia-induced neuroapoptosis and offers some of neuroprotective strategies that could be beneficial as adjunct therapy in preventing anesthesia-induced death of developing neurons in the neonates. A randomized literature search was carried out using search words apoptosis, general anesthetics, and developing brain from 1979 to 2011 for effects of general anesthetics on developing brain in PUBMED and relevant published literature reviewed. General anesthetics may produce neurotoxicity and enduring cognitive impairment in young and aged animals, but the issue has not been adequately studied in humans. It is premature to recommend a change clinical practice based on the present data.